Analisis Bibliometrik Promosi Kesehatan Selama Masa Pandemi COVID-19 Menggunakan VOSviewer - Rohmayanti Rohmayanti; Retna Tri Astuti (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional, 2023)
ABSTRACT This study aims to analyze trends in the scope of research on health promotion during the COVID-19 pandemic. The method used is a bibliometric review process: article searches through Harzing's Publish or Perish, and from the Google Scholar database, data mapping is then carried out using VOSviewer. The results showed that the number of publications on search results regarding health promotion via Google Scholar during the COVID-19 pandemic in 2020–2022 was 18 articles involving 12 countries. Five articles were published in 2020, 11 articles were published in 2021, and 2 articles appeared in early 2022. A search with the keyword